Silicone hydrogels materials for contact lens applications - González-Méijome, José Manuel (2014)
Silicone hydrogel (Si-Hy) materials combine the benefits of silicone or siloxane derivates in terms of oxygen permeability and mechanical properties with those of hydrogels in terms of wettability and hidrophilicity. Such properties are critical when it comes to the application at the ocular surface in the form of contact lenses (CL) to correct visual dysfunctions, as bandage mechanism or as drug delivery devices. Nowadays, CL are used by over 100 million people worldwide.Silicone hydrogel materials applied in the production of CL are a good example of how challenging the ocular surface environment is when it comes to the engineering of devices that will be well tolerated in this part of the human body. We now face the challenge of understanding the interaction between these materials and the disinfecting and cleaning systems, how these can impact the integrity of the ocular surface and the risks of inflammatory adverse events, and how wearing comfort can be improved.